Avaliação da usinabilidade de ligas AL-SI-MG em função das condições de solidificação e tratamentos térmicos - Machado, Pedro Augusto Bottlender (2021)
The main objective of the present work is to analyze the machinability, in the turning process, of as-cast Al-Si-Mg ternary alloys with 0.6% Mg and 3%, 7% and 12% Si contents (wt.%), as well as after heat treatments by solutioning and artificial aging (T6). Three alloys were confectioned, named as 316 (Al-12% Si-0.6Mg), 376 (Al-7% Si-0.6Mg) and 336 (Al-3% Si-0.6Mg). Ingots of each alloy were obtained in an ascending vertical directional solidification apparatus using a base-cooled cylindrical metallic mold instrumented with thermocouples. Samples extracted from the ingots were characterized by metallographic techniques using macroscopy, optical microscopy (OM), scanning electron microscopy (SEM) and dispersive energy spectroscopy (EDS). The mechanical properties were evaluated by tensile strength, hardness and microhardness tests, before and after the heat treatments. After characterization, specimens were submitted to machinability tests as a function of cutting force within the turning process, using parameters such as depth of cut, cutting speed, geometry and tool material fixed during all tests. The results obtained allowed to establish relations between the solidification conditions, microstructural formation and the machinability of the investigated alloys. With different chemical compositions, different values of solidification speed, thermal gradient, and cooling rate were observed, influencing the appearance of larger secondary dendritic arms in alloys 336 EBF and 376 EBF but smaller for alloy 316 EBF and different microstructures for each alloy. Similar hardness values were found for alloys 336 EBF and 376 EBF, and higher values for alloy 316 EBF. The values of the cutting force Fc and hardness were altered by the conditions of each material (raw melting state and post heat treatment).